Chinese spatial strategies : imperial Beijing, 1420-1911 - Zhu, Jianfei, 1962- (RoutledgeCurzon, 2004)
Presents a study of social spaces of the capital of Ming Qing China (1420-1911). Focusing on early Ming and early and middle Qing, it explores architectural, urban and geographical space of Beijing.